MILLENNIALS: THEIR FINANCIAL LITERACY AND DECISION MAKING - Arie Widyastuti; Ratna Komara; Layyinaturrobaniyah Layyinaturrobaniyah (Dinasti International Journal of Education Management And Social Science, 2020)
Millennials are now the largest population groupings in Indonesia, therefore their decisions in financial matters have significant implications for themselves as well as the country’s economy. This paper is aimed to evaluate the level of financial literacy possessed by the Millennials and their attitudes towards making key financial decisions. Data were collected through questionnaire of 30 questions with 15 questions regarding financial literacy and 15 questions related to financial decision making, with the participants in the study consists of 446 individuals who were born from 1980s to 2000s. The result reveals that better financial literacy leads to better financial decision at 1% significance level. This study also indicates that, although demographic profiles such as gender, education, length of working experience, income, number of credit card ownership and mother education have positive correlation with the level of financial literacy, they do not have moderating effect to the financial literacy and financial decision making of the millennials